AB0706 ASSOCIATION BETWEEN SARCOIDOSIS AND SPONDYLOARTHRITIS: A NEW COMORBIDITY, CHANCE OR SELECTION ERROR? (TREND-ESPA STUDY). (2nd June 2020) - Mazzucchelli, R.; Crespí-Villarías, N.; Almodovar, R.; Perez-Fernandez, E.; Quirós, J.; Zarco-Montejo, P.
Abstract : Background: On literature there are a significant number of cases describing the coexistence between Spondyloarthritis (Spa) and sarcoidosis. There are 3 main ways in which different diseases can be found in the same individual: chance, selection bias, or by 1 or more types of causal association. In this work we analyze whether there is a causal association between sarcoidosis and Spa. Objectives: To analyze the hypothesis that there is a causal association between sarcoidosis and Spa. Methods: Case-control study nested in a population database of hospital admissions (CMBD). Period: 1999 to 2015. Database Study (DB): Study population + control population. Study population: patients with a diagnosis of Spa who were admitted to any national hospital. Control population (GP): group of the general population (without Spa diagnosis) matched of equal sex, age, year of admission as the study population. Cases: Cases of sarcoidosis were identified by the presence of ICD-9 code 135. Controls: admissions without sarcoidosis diagnosis. The clinical-demographic characteristics of patients with Spa and sarcoidosis vs Spa without sarcoidosis are described. To rule out the association being random, the Odds Ratio (OR) was calculated for the association between sarcoidosis and Spa. To minimize selection error, the association with logistic regression models was analyzed by adjusting by more than 50 variables. Results: The DB of the study consists of 205, 218 admissions: 102, 609 admissions with Spa and 102, 609 admissions without Spa. There was a total of 220 admissions with sarcoidosis: 133 (0.12%) in Spa and 87 (0.08%) in the GP group. The OR is 1.53 (IC95% 1.17 – 2.01). The following table shows the main clinical-demographic characteristics of patients with Spa and sarcoidosis versus the rest of Spa: In the logistic regression model (model 1) adjusting by age, sex, and year of admission the OR was 1, 459 (IC95% 1.10-1.92). Model 2: Adjusting by model 1 variables + those that were significant in the univariate analysis (EN and HBV) the OR was 1.40 (IC95% 1.06-1.84). Finally, in Model 3, which included model variables 2 + those variables with clinical meaning (out of a total of 50 variables) the OR was 1.38 (IC95% 1.04-1.82). Conclusion: There is a causal association between sarcoidosis and Spa (OR 1.5). This association is ruled out by chance. Although selection bias cannot be completely ruled out, it is reasonably minimized in our study. Disclosure of Interests: Ramón Mazzucchelli: None declared, Natalia Crespí-Villarías: None declared, RAQUEL ALMODOVAR Speakers bureau: Abbvie, Celgene, Janssen, Lilly, Novartis, Pfizer., Elia Perez-Fernandez: None declared, Javier Quirós: None declared, Pedro Zarco-Montejo Speakers bureau: Abbvie, MSD, Novartis, Pfizer.